Development of preliminary six sigma framework for Malaysian manufacturing company - Siman, Aslina (2012)
In today’s industrial climate, manufacturing companies need to find and use any approach that will help them work smarter and achieve higher performance level to compete effectively in the global market. Although the overall average efficiency and quality levels have risen, companies are now hitting a “glass ceiling”; with their existing improvement efforts having little impact on often deep rooted quality issues. Appropriately applying the Six Sigma approach and toolset is, as a growing number in manufacturing companies already found, it is a good way for working smarter. The standard Six Sigma deployment protocol, are acceptable for large organizations, but way beyond Small and Medium Enterprise (SME) organizations. Without having a basic framework as a guideline and help from expert such as consultants, companies that are interested in implementing Six Sigma are having difficulties in identifying and understanding the implementation process needed. This study aims to examine success factors and to develop a framework on how to implement Six Sigma. A questionnaire was used as one of the research tools and it was developed based on established literature. A total of 239 questionnaires were distributed. The response rate is 22.18 percent. The survey results from this study show that 28.3 percent of the manufacturing companies have already implemented Six Sigma for an average period of 5.3 years.Some impeding barriers highlighted in Six Sigma implementation are high entry cost,no dedicated resources and no clear mandate from top management. Case studies in some selected manufacturing companies were carried out whereby comparisons were conducted between the existing framework and actual practices. Actual practices vary depending on the practitioner knowledge and guidelines from the top management. Out of five case study companies, company D shows to have the biggest impact and benefits from Six Sigma implementation whereby they have achieved an average saving of RM 5 Million per year and having a good system and an organization wide real time communication. Based on literature review, survey result and case studies, Six Sigma implementation framework was developed accordingly. It consists of a step by step procedure from initial implementation until the successful Six Sigma project implementation stage, together with some tips, information and examples that need to be emphasized or aware off. This research seeks to conclude that a strategic Six Sigma framework for Malaysia manufacturing company as a guide so that Six Sigma can be effectively implemented, subsequently utilized and deliver business benefits to Malaysia manufacturing companies.